Genome-wide association study on liver function tests in Chinese - Yidan, Sun; Zizhao, Tian; Wei, Zhou; Mo, Li; Cong, Huai; Lin, He; Shengying, Qin (Yíchuán, 2021)
Liver function tests (LFTs) measure a series of complex traits that are affected by genetic and environmental factors. Previous studies demonstrated that there exist significant differences in LFTs across individuals, which may be the results of the unique genetic profile of each individual. Therefore, we performed a genome-wide association study (GWAS) to evaluate the influence of single nucleotide polymorphisms (SNPs) in LFTs and identify the significant association between genotypes and phenotypes using 1653 Chinese subjects from the UK Biobank database. We successfully identified 229 SNPs significantly associated with total bilirubin (TB) levels, 27 SNPs significantly associated with alkaline phosphatase (ALP), and 36 SNPs significantly associated with γ-glutamyl transpeptidase (GGT) in serum. In addition, one SNP significantly associated with aspartate transaminase (AST) in serum was also found. Among the most significant ones, the topmost 11 SNPs were found to be associated with LFTs for the first time. Through functional genomic analysis, the clinical significance of these SNPs could be associated with diseases (e.g. Gilbert's syndrome) and the respective candidate genes (UGT1A, ABO, GGT1). This study provides a preliminary rationale for research to understand the associations of individual genetic differences and clinical liver functions in the Chinese population.